2017
DOI: 10.1177/0165551516687701
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Twitter use by major LIS professional organisations in the United States

Abstract: Although Twitter has been widely adopted by professional organisations, there has been a lack of understanding and research on its utilisation. This article presents a study that looks into how five major library and information science (LIS) professional organisations in the United States use Twitter, including the American Library Association (ALA), Special Libraries Association (SLA), Association for Library and Information Science Education (ALISE), Association for Information Science and Technology (ASIS&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This approach can not only identify prevalent discussion topics, but also map the relationships between topics. The co-hashtag analysis reveals that the trending topics users discussed were very diverse and broader in scope compared to the topical analysis of tweets initiated by the previous study (Zhang et al, 2018), showing the value and importance of contextual analysis of the LIS professional organizations in the Twittersphere presented in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This approach can not only identify prevalent discussion topics, but also map the relationships between topics. The co-hashtag analysis reveals that the trending topics users discussed were very diverse and broader in scope compared to the topical analysis of tweets initiated by the previous study (Zhang et al, 2018), showing the value and importance of contextual analysis of the LIS professional organizations in the Twittersphere presented in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 64%
“…Twitter provides new opportunities for libraries and institutions to reach out to targeted audiences and provide information regarding hours of operation, events, services, and resources (Carscaddon & Chapman, ; Milstein, ). While previous research has investigated Twitter use by businesses, there has not been much examination of library and information science (LIS) professional organizations in social media (Zhang, Sheu, & Zhang, ). Additionally, previous research mainly focused on what LIS organizations, especially libraries, talk about (Del Bosque, Leif, & Skarl, ; Shiri & Rathi, ; Zhang et al, ), with no consideration of tweets by others regarding major LIS professional organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Queries, opinions, and feedback seeking were the least tweeted about. Zhang, Sheu, and Zhang (2018), in their investigation of the thematic categories of five LIS professional organizations' tweets, found that the largest category was library activities and services, which includes themes such as library users and usage, book recommendations, and hours and operations. In an examination of different platforms, Phillips (2015) investigated how the libraries' professional roles were demonstrated to their patrons via Facebook.…”
Section: Insert Fig 2 Here Nyc Public Libraries General Content On Twittermentioning
confidence: 99%
“…Next, with the popularity of social media, channels such as Twitter, Weibo, and WeChat -with massive number of users -have become key channels for information release. Zhang, Sheu and Zhang (2018) studied how five major library and information science (LIS) professional organizations in the United States use Twitter to release information for interaction. Kim, Lee, Shin and Yang (2017) studied the impact of travel information on the decisions made by users and marketers released on Weibo.…”
Section: Information Releasementioning
confidence: 99%